How much data can we anticipate? Incrementality and unlimited interactivity in sentence comprehension - Sękowska, Jolanta (Acta Universitatis Lodziensis. Folia Germanica, 2017)
This paper discusses the issue of the boundaries of incrementality in sentence-comprehension processes.The maximum incrementality, postulated as unlimited interactive sentence-comprehension models, allows anticipation and prediction top-down processing, facilitating quick interpretation of the perceived linguistic input. However, it involves a substantial strain on cognitive resources, especially at the beginning of the sentence. In addition, in the case of structures with verbs placed at the end of a sentence, unlimited interactivity keeps vast knowledge resources active until the verb and its arguments are agreed.This imposes a certain order of importance on interactive models at the same time assigned to the ongoing top-down processing, thus limiting incrementality, interactivity and the ability to anticipate.